Lake and Pond Management Guidebook - McComas, Steve (CRC Press, 2009)
The Lake and Pond Management Guidebook is the successor to the bestselling Lake Smarts: The First Lake Maintenance Handbook, the "bible" for small-scale lake and pond improvements, published by the Terrene Institute in 1993.